A new experimental approach to determination of critical depth in high speed machining of soda-lime glass - Mahmud, M.A; Nurul Amin, A.K.M; Arif, M. D. (Trans Tech Publications, Switzerland, 2012)

(untitled)
Abstract. Soda-Lime glass is a very hard and brittle material which is commonly used as window panels and many other common applications. Due to its low fracture toughness it is very difficult to machine and obtain good surface finish under nornal cutting conditions. Hence, machining has to be done in ways to avoid brittle fracture on the finished machined surface. Such machining is only possible under ductile mode machining conditions when the removal of material is performed in the plastic state. However, ductile mode machining requires that during machining the temperature generated in the cutting zone in the working temperature range of glass to avoid crack formation during machining. This makes all types of machining of glass an extremely challenging affair, given the current state and mode of mechanical machining. This research paper elucidates the results of an experimental study for determination of critical depth of cut as a function of cutting parameters in high speed end milling of soda-lime glass. The critical depth is defined as the depth of cut at which crack formation the material is initiated for a given high speed attachment. In determining the critical depth as well as the ductile brittle transition depth, machining was performed on a tapered surface. Vibration signals from an accelerometer in time domain (amplitude vs. time display) and the surface characteristics were used in identifying the critical depth of cut. The new method has been found to be useful in online determination of the critical depth, as well as the brittle-ductile transition depth, for generating crack-free surfaces with good surface finish in high speed end milling of soda lime glass.